187k views
1 vote
Solve the radical equation, if possible. √3x-1+1=√3x+6

1 Answer

3 votes

Answer:

x = 3 1/3

Step-by-step explanation:

This is solved nicely using a graphing calculator. It shows the solution as x = 3 1/3.

_____

If you want to solve it by hand, you can square both sides of the equation. This gives ...

... 3x -1 +2√(3x -1) +1 = 3x +6

Subtracting 3x gives

... 2√(3x -1) = 6

... √(3x -1) = 3 . . . . . divide by 2

... 3x -1 = 9 . . . . . . . square both sides (again)

... 3x = 10 . . . . . . . . add 1

... x = 10/3 = 3 1/3 . . . . divide by 3

The solution is x = 3 1/3.

Solve the radical equation, if possible. √3x-1+1=√3x+6-example-1
User Sunil Lama
by
6.2k points